Students’ Ability and Difficulties in Writing at the Tenth Grade - Lollo Rosa lLubis; Evan Afri (International Journal of English and Applied Linguistics (IJEAL), 2023)
The tenth-grade students in Indonesia had difficulties in writing and this was the background in conducting the study. EFL Indonesia was one of the factors why students in EFL Indonesia had difficulties in writing. There were some indicators to determine students’ ability in writing. This study used five indicators which included content, organization, grammar, vocabulary and style & quality. The approach of the research used a mixed method (combined quantitative and qualitative data). Quantitative data was collected by using a test sheet. This instrument was used to measure students’ ability in writing. Furthermore, qualitative data was collected by interview. This instrument was used to describe students’ difficulties in writing.  The subjects of the research consist of 20 students of High School and they were taken by using a random sampling technique. After collecting the data, quantitative data (test sheet) showed an average of 50.7. This score was an unacceptable-not category (below average). Furthermore, the students’ difficulties in writing included internal factors and external factors. The first factors included the lack of organization, developing ideas, grammar, and vocabulary. Meanwhile, the second factor included English learning time was being very short, daily life, and inaccurate curriculum in learning writing.